2019
DOI: 10.1016/j.marenvres.2019.104787
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approach indicates consumption of jellyfish by commercially important fish species in a coastal Mediterranean lagoon

Abstract: Until recently, jellyfish have been ignored as an important source of food, due to their low nutritional value. Here, quantitative PCR was used to detect and quantify the DNA of the jellyfish Aurelia coerulea in the gut contents of commercially important fish species from the Thau Lagoon. Individuals from five fish species were collected during two different periods: the bloom period, when the pelagic stages of A. coerulea are abundant, and the post-bloom period, when only the benthic stagepolypsis present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Biochemical (stable isotope or fatty acid analysis) or genetic probes may be used to alleviate some of the underreporting of gelatinous tissue in fish predator stomachs (e.g. van der Bank et al 2011, Cardona et al 2012, D'Ambra et al 2015, Lamb et al 2017, Marques et al 2019); however, these methods generate binary data and cannot be used to determine magnitude (e.g. percent by number or weight: %N, %W).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical (stable isotope or fatty acid analysis) or genetic probes may be used to alleviate some of the underreporting of gelatinous tissue in fish predator stomachs (e.g. van der Bank et al 2011, Cardona et al 2012, D'Ambra et al 2015, Lamb et al 2017, Marques et al 2019); however, these methods generate binary data and cannot be used to determine magnitude (e.g. percent by number or weight: %N, %W).…”
Section: Discussionmentioning
confidence: 99%
“…fishes: 14.8–39.3 kJ g −1 DW, crustaceans: 7.1–25.3 kJ g −1 DW, squid: 16.2–24.0 kJ g −1 DW; Schaafsma et al., 2018 ) owing to their high inorganic content. Despite their low energy content, recent studies have shown that jellyfish are consumed by many organisms throughout the marine food chain ( Marques et al., 2019 ). Their high water content allows jellyfish biomass to be quickly digested (e.g.…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…These high-throughput amplicon sequencing technologies have extremely high detection sensitivity and bypass the biases posed by visual methods. Recently, the application of DNA metabarcoding to marine predator gut contents has demonstrated the capacity of these methods to detect gelatinous prey [18][19][20][21][22]. In the study of gelatinous zooplankton as consumers, this technology has only been applied to assess the microbial diet of the tunicate Salpa thompsoni [23], the predatory diet of the scyphomedusa Aurelia coerulea [24], and the diet of the lobate ctenophore Mnemiopsis leidyi [25].…”
Section: Introductionmentioning
confidence: 99%